Sustainable Renovation of Traditional Housing Architecture of the Thai Ethnic Group in the Northwestern Region of Vietnam - Tran, Quoc Bao; Le, Tien Thuan; Dang, Viet Long; Dao, Quynh Anh (International Journal of Sustainable Construction Engineering and Technology, 2025)
The traditional housing of the Thai ethnic group in the Northwestern region of Vietnam not only serves as a living space but also embodies distinctive cultural, historical, and ecological values. However, due to the impact of socio-economic transformation and modernization, this architectural type is at risk of disappearing. This study aims to assess the current state, community awareness, and directions for renovating traditional Thai housing in a sustainable manner. Through field surveys, in-depth interviews, and the development of three pilot renovation plans in the Vang Pheo village, the study proposes a community-based sustainable renovation approach that preserves the core values of traditional architecture while improving living conditions. The results contribute to the academic discourse on sustainable heritage regeneration, as well as providing practical suggestions for local policies and architectural practices.